2015
DOI: 10.1039/c4cc06443g
|View full text |Cite
|
Sign up to set email alerts
|

Studying localized corrosion using liquid cell transmission electron microscopy

Abstract: Localized corrosion of Cu and Al thin films exposed to aqueous NaCl solutions was studied using liquid cell transmission electron microscopy (LCTEM). We demonstrate that potentiostatic control can be used to initiate pitting and that local compositional changes, due to focused ion beam implantation of Au(+) ions, can modify the corrosion susceptibility of Al films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 28 publications
0
54
0
Order By: Relevance
“…Recent studies have also identified alternative factors that may also affect the liquid during in situ aqueous experiments; these studies have primarily concentrated on the electron beam/liquid interaction such as the reported generation of H 2 bubbles (Grogan et al, 2013). In other studies investigators were primarily concerned with nanoparticles, nanowires, or sputtered thin films located between two SiN x windows, resulting in the creation of partially or fully filled chamber of aqueous solution, all of which differ from the specimens used in this work (de Jonge et al, 2010;Woehl et al, 2012Woehl et al, , 2013Chee et al, 2015;Schilling et al, 2015). In these cases, the volume ratio of nanoparticles and electrolyte is small compared with a conventional bulk electrochemical experimental cell, which is comprised of a larger metal specimen and surrounding electrolyte.…”
Section: In Situ Aqueous Studies: Corrosion Basicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have also identified alternative factors that may also affect the liquid during in situ aqueous experiments; these studies have primarily concentrated on the electron beam/liquid interaction such as the reported generation of H 2 bubbles (Grogan et al, 2013). In other studies investigators were primarily concerned with nanoparticles, nanowires, or sputtered thin films located between two SiN x windows, resulting in the creation of partially or fully filled chamber of aqueous solution, all of which differ from the specimens used in this work (de Jonge et al, 2010;Woehl et al, 2012Woehl et al, , 2013Chee et al, 2015;Schilling et al, 2015). In these cases, the volume ratio of nanoparticles and electrolyte is small compared with a conventional bulk electrochemical experimental cell, which is comprised of a larger metal specimen and surrounding electrolyte.…”
Section: In Situ Aqueous Studies: Corrosion Basicsmentioning
confidence: 99%
“…Chee et al (2015) deposited a thin Al layer with Au on an electrochemical SiN x window, to measure the galvanic corrosion in a 0.01 mol NaCl electrolyte. Their study demonstrated that it was possible to measure the electrochemical behavior of the interface between sputtered Al and the electrolyte for pit initiation and galvanic corrosion.…”
Section: In Situ Aqueous Studies: Previous Workmentioning
confidence: 99%
“…Metals in contact with aqueous solutions, depending on their surface morphology, undergo different modes of corrosion [2]: general, pitting, crevice, inter-granular, galvanic, and erosion corrosion, environmentally induced fracture, and dealloying. In spite of its importance, many aspects of localized corrosion of metals are not well understood [3], probably because it is often difficult to monitor the corrosion processes at high spatial resolution under a liquid layer. Liquid cell transmission electron microscopy (LC-TEM), coupled with electrochemical control and analytic functions, enables the observation of structural changes and chemical processes in liquid phases.…”
mentioning
confidence: 99%
“…Liquid cell transmission electron microscopy (LC-TEM), coupled with electrochemical control and analytic functions, enables the observation of structural changes and chemical processes in liquid phases. It provides a combination of temporal and spatial resolution that is difficult to achieve using other characterization techniques [4], and has yielded detailed information on corrosion kinetics in liquid solutions [3,4].…”
mentioning
confidence: 99%
“…Precise engineering of the final morphology relies on a deep understanding of the reaction pathways involved. Although ex situ microscopies provide critical information, the ability to record the process as it takes place is expected to contribute to a deeper understanding [4]. Liquid cell TEM, especially when coupled with electrochemical control and analytical capabilities, provides the needed tool for measuring structural and chemical changes in liquids [4][5][6].…”
mentioning
confidence: 99%